The Word Hijab and Khimar in the Qur'an: A Double Movement Hermeneutic Analysis Fazlur Rahman - Maisurah, Fida Layly; Rahman, Habibur; Nahri, Delta Yaumin; Asma'i, Ali Mahmud (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The Problem of the boundaries of genitalia and proper dress code for women are still become a crussial issue that must always be considered and studied. As a attention and privilege for women in Islam and The Quran, there is a letter which is taken from the word “women”. It’s called surah an-Nisa’. The form of Islamic concern is also contained in the study of verses of the hijab and khimar which include the rulesfor covering the women’s genitals are found in two different letters. namely, QS. an-Nur (24): 31, and QS. al-Ahzab (33): 59. The use of terms hijab and khimar in the two verses have their respective similarities and differences. The method used in this study is a qualitative approach with a descriptive-analytical-thematic method. In this study, the author compiles verses about the jilbab and khimar by referring to the book al-Mu’jam al-Mufahras li Alfāẓi al-Qur’ān.then examines the translitation and interpretation of verses using a classical and contemporary era interpretation.Then analyze the interpretation using Fazlur Rahman’s double movement hermeneutic theory. The result of this study are: first, there are two verses in different letters regarding the terms jilbab and khimar. Namely QS. an-Nur (24): 31, and QS. al-Ahzab (33): 59. Second, there are similarities and differences between the interpretation of the classical era and also the contemporary era regarding the rules of jilbab and khimar in the Quran. Third, the moral ideal of this study is that Muslim wmen have an equal position. Likewise with men. The honor and nobility of women in the current context is given more attention than in one context in jahilia era. The specific law of the study of the term jilbab dan khimar is thah the syariat of jilbab dan khimar is not only to cover the private parts. But also that are non-physical must also be considered by closing the heart and mind from commiting immorality.